Resources, Conservation & Recycling - Resources, Conservation & Recycling (Elsevier, 2026)
The journal Resources, Conservation & Recycling welcomes contributions from research, which consider sustainable management and conservation of resources. The journal emphasizes the transformation processes involved in a transition toward more sustainable production and consumption systems. Emphasis is upon technological, economic, institutional and policy aspects of specific resource management practices, such as conservation, recycling and resource substitution, and of "systems-wide" strategies, such as resource productivity improvement, the restructuring of production and consumption profiles and the transformation of industry.
FI 1.64
Q1
Keywords: Earth; Space & Environmental Sciences; Sustainable Development; Ciencias de la tierra; Desarrollo sustentable; Acuerdos transformativos; Transformative agreements; Gestión sostenible; Conservación de los recursos; Conservación, reciclaje y sustitución de recursos